Mesoporous Silica Promotes Osteogenesis of Human Adipose-Derived Stem Cells Identified by a High-Throughput Microfluidic Chip Assay - Xin Chen; Chao Wang; Min Hao; Hang Zhao; He Xia; Liyang Yu; Dong Li; Jichuan Qiu; Haijun Li; Lin Han; Yuanhua Sang (MDPI AG, 2022)
Silicon-derived biomaterials are conducive to regulating the fate of osteo-related stem cells, while their effects on the osteogenic differentiation of human adipose-derived stem cells (hADSCs) remain inconclusive. Mesoporous silica (mSiO2) is synthesized in a facile route that exhibited the capability of promoting osteogenic differentiation of hADSCs. The metabolism of SiO2 in cells is proposed according to the colocalization fluorescence analysis between lysosomes and nanoparticles. The released silicon elements promote osteogenic differentiation. The detection of secretory proteins through numerous parallel experiments performed via a microfluidic chip confirms the positive effect of SiO2 on the osteogenic differentiation of hADSCs. Moreover, constructed with superparamagnetic iron oxide (Fe3O4), the magnetic nanoparticles (MNPs) of Fe3O4@mSiO2 endow the cells with magnetic resonance imaging (MRI) properties. The MNP-regulated osteogenic differentiation of autologous adipose-derived stem cells provides considerable clinical application prospects for stem cell therapy of bone tissue repair with an effective reduction in immune rejection.